2017
DOI: 10.1038/labinvest.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

Papillary renal cell carcinoma-derived chemerin, IL-8, and CXCL16 promote monocyte recruitment and differentiation into foam-cell macrophages

Abstract: Papillary renal cell carcinoma (pRCC) is the second most common type of renal cell carcinoma. The only curative treatment available for pRCC is radical surgery. If the disease becomes widespread, neither chemo- nor radiotherapy will have therapeutic effect, hence further research on pRCC is of utmost importance. Histologically, pRCC is characterized by a papillary growth pattern with focal aggregation of macrophages of the foam cell phenotype. In other forms of cancer, a clear role for tumor-associated macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
3
23
0
2
Order By: Relevance
“…This is opposite to the majority of tumors that display decreased chemerin . While there is little information regarding the potential impact of elevated chemerin expression in renal carcinoma, a recent study sheds some light on the matter [107]. pRCC accounts for approximately 20% of all renal cancers.…”
Section: Renal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…This is opposite to the majority of tumors that display decreased chemerin . While there is little information regarding the potential impact of elevated chemerin expression in renal carcinoma, a recent study sheds some light on the matter [107]. pRCC accounts for approximately 20% of all renal cancers.…”
Section: Renal Carcinomamentioning
confidence: 99%
“…A unique feature of pRCC is the focal aggregation of foam cell macrophages inside the papillae. In the study by Krawczyk et al, foamy macrophages were histologically identified in 82% of pRCC tumors and the macrophages expressed cell surface markers CD689 and CD163 that are characteristic of the M2 anti-inflammatory phenotype [107]. The researchers hypothesized that the pRCC cells must secrete factors that recruit monocytes and contribute to their differentiation into foamy macrophages.…”
Section: Renal Carcinomamentioning
confidence: 99%
“…It mainly functions as a scavenger receptor for oxidized low‐density lipoprotein (oxLDL), and as an adhesion molecule for cells expressing CXCR6 . The soluble form of CXCL16 is produced by constitutive or inducible cleavage of the transmembrane form, and this is involved in inducing the homing process of several leukocytes, including monocytes, T‐lymphoid cells, and natural killer (NK) cells …”
Section: Introductionmentioning
confidence: 99%
“…8,9 The soluble form of CXCL16 is produced by constitutive or inducible cleavage of the transmembrane form, and this is involved in inducing the homing process of several leukocytes, including monocytes, T-lymphoid cells, and natural killer (NK) cells. 7,8,[10][11][12] The maternal-fetal interface expresses a variety of chemokines and their receptors, including CCL1, CCL3, CCL4, CCL9, CXCL6, and CXCL12, which form a complex network that precisely regulates the proliferation and differentiation of trophoblasts. [13][14][15] In addition, chemokines are involved in the recruitment and differentiation of immune cells, processes that are essential to maintain the special immune microenvironment at the maternal-fetal interface.…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 could induce the chondrogenic differentiation of bone marrow mesenchymal stem cells in vivo and in vitro through the PI3k/AKT cell signaling pathway (Yang et al, 2018). The secretion of IL-8, chemerin, and CXCL16, by papillary renal cell carcinoma, promoted the recruitment of monocytes and the differentiation of macrophages with foam cell phenotype (Krawczyk et al, 2017). IL-8 and GM-CSF were required in the differentiation of acute monocytic leukemia induced by CD44 (Delaunay et al, 2008).…”
mentioning
confidence: 99%